Identifikasi dan Pemetaan Masalah di Nagari Pasca Bencana Erupsi Gunung Marapi di Sumatera Barat - Mahdi, Mahdi; Istijono, Bambang; Yossafra, Yossafra; Ismail, Febrin Anas; Hakam, Abdul; Adji, Bayu Martanto; Saputra, Dendi; Andriani, Andriani; Narny, Yenny; Giffari, Muhammad Al; Zis, Sirajul Fuad; Yuliet, Rina (Universitas Batanghari Jambi, 2025)
Mount Marapi is an active volcano located in West Sumatra. The eruptions of Mount Merapi have a significant impact on the social and economic conditions of the surrounding communities. This study aims to identify and map the post-disaster issues in the nagari affected by the eruption of Mount Marapi in West Sumatra Province to formulate appropriate mitigation measures. Using a descriptive qualitative approach with a case study method, data were collected through direct observation, in-depth interviews, and photographic documentation. The results of the study show that infrastructure damage, including roads and bridges, hinders mobility and aid distribution, while the agricultural and livestock sectors suffer substantial losses. The social impacts include loss of housing and psychological trauma, while the economic impacts are evident in the significant losses faced by small and medium enterprises (SMEs). Health concerns, such as increased respiratory and skin diseases, as well as sanitation issues, are also major concerns. Mitigation efforts undertaken include infrastructure repairs, construction of embankments, public education on disaster preparedness, and psychological support for disaster victims. This study highlights the importance of comprehensive and sustainable mitigation strategies to reduce the impact of disasters and ensure the well-being of communities in disaster-prone areas.